State‐of‐the‐art analytical approaches and strategies to assess disposal of drugs for wastewater‐based epidemiology. Issue 1 (22nd June 2022) - Quireyns, Maarten; Boogaerts, Tim; Van Wichelen, Natan; Covaci, Adrian; van Nuijs, Alexander L. N.
Abstract: Not all residues of drugs found in influent wastewater are the result of consumption. Identifying intentional or accidental disposal is crucial in wastewater‐based epidemiology to ensure the accuracy of observed spatiotemporal trends in consumption patterns. So far, only a limited number of studies provided analytical evidence for the direct disposal of illicit drugs or pharmaceuticals. Additionally, only minimal standardization in the workflow is employed to distinguish direct disposal from consumption. PubMed, SCOPUS, and Web of Science databases were searched using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA, 2020) guidelines. The search focused on wastewater‐based epidemiology publications in which the dumping event was strongly suspected or identified through (i) parent compound‐metabolite ratios, (ii) enantiomeric profiling, and (iii) nontarget and suspect screening. In total, 29 studies were included in this systematic literature review. This study aims to review existing approaches to assess direct disposal of drugs in influent wastewater, review literature for potential dumping events, and proposes a simple evidence‐based scoring system for the identification of direct disposal of drugs in influent wastewater, based on available analytical evidence. This framework is a first effort to standardize dumping/disposal assessment, while more research is needed to further refine the decision criteria and analytical techniques used within the proposed strategy. This article is categorized under: Toxicology > Drug Analysis Toxicology > Analytical Abstract : Strategies in wastewater‐based epidemiology to assess disposal of illicit drugs.